Optimizing some factors affecting alkaline protease production by a marine bacterium Teredinobacter turnirae under solid substrate fermentation - Elibol, M; Moreira, AR (Elsevier Sci Ltd, 2005)
Production of extracellular alkaline protease by a shipworm bacterium Teredinocabcter tumirae, under solid substrate fermentation (SSF) was optimised. Soybean was used as a sole carbon and/or nitrogen source. The maximum protease yield (1950 U/ml) was achieved with optimised parameters such as coarse size of soybean (2 mm), concentration of soybean 1% (w/v), unadjusted pH of the medium 7.34, inoculurn level 2.5% (v/v) and agitation rate 120 rpm. Sixty percent of higher production was achieved after optimising the process parameters. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: solid substrate fermentation; soybean; alkaline protease; Teredinobacter turnirae